Website Development of Information System Study Program UNSRAT as A Media Information - Pagewang, Yalon Bu'tu; Pinontoan, Benny; Lapihu, Dodisutarma; Latumakulita, Luther Alexander; Takaendengan, Mahardika Inra; Ngangi, Stephano Caesar Wenston; Montolalu, Chriestie Ellyane Juliet Clara (Universitas Teknokrat Indonesia, 2025)
Although the Information Systems Study Program at UNSRAT had an existing website, it failed to effectively deliver up-to-date and comprehensive academic information. Both students and the broader community often experienced difficulties in accessing essential program-related content. In addition, the site's visual design was deemed unattractive and did not meet user expectations. objective of this research is to design and implement a more interactive and informative website to enhance the efficiency of academic information dissemination. This study employs the Rapid Application Development (RAD) methodology, encompassing requirement analysis, system design through UML diagrams and wireframes, system implementation using the CodeIgniter framework, and functionality testing via the black-box testing approach. The findings revealed that all implemented website features operated as intended and aligned with user requirements. Furthermore, analysis of feedback from 70 respondents yielded an average rating of 4.1 out of 5.0, indicating that the website successfully met user expectations regarding accessibility, visual design, content relevance, and overall technical performance.